2018
DOI: 10.3390/su10020485
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Water Withdrawals in the Tiber River Basin (Central Italy)

Abstract: Problems in the sustainable exploitation of water resources are mainly due to the spatial distribution of uses and are worsened by uncontrolled withdrawals by different activities. In this context, in order to evaluate and manage the available water resources, a decision support system has been developed to support the decision-making processes. This system was implemented on a web platform, in order to manage spatial data and to analyze information on water resources. The system also integrates a WEB-GIS engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The observed FDC, natural FDC, and estimated natural FDC were calculated for each case study basin; in particular, the observed FDC was obtained from time-series data of hydrometric stations in terms of the average FDC (as per Vogel and Fennessey [49]), the natural FDC was obtained from natural daily flow time-series reconstruction by means of observed data and abstractions data [42] and, finally, the estimated natural FDC was the result of the proposed regionalization technique. Figures 4-6 show a comparison between these three types of FDC, where the observed FDC was always clearly majorly influenced by water abstractions (particularly at the end of the FDC), as the irrigation water abstractions had a heavy influence on the monitored flow and depressed the curve irregularly.…”
Section: Case Study and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed FDC, natural FDC, and estimated natural FDC were calculated for each case study basin; in particular, the observed FDC was obtained from time-series data of hydrometric stations in terms of the average FDC (as per Vogel and Fennessey [49]), the natural FDC was obtained from natural daily flow time-series reconstruction by means of observed data and abstractions data [42] and, finally, the estimated natural FDC was the result of the proposed regionalization technique. Figures 4-6 show a comparison between these three types of FDC, where the observed FDC was always clearly majorly influenced by water abstractions (particularly at the end of the FDC), as the irrigation water abstractions had a heavy influence on the monitored flow and depressed the curve irregularly.…”
Section: Case Study and Resultsmentioning
confidence: 99%
“…WEB-GIS of water abstractions [42] serves the main instrument to implement the evaluation of the term "abstractions minus returns" in Equations (1) and (3). In fact, for existing water abstractions, an analysis procedure has been developed which, starting from the point selected directly by clicking on the map, finds the upstream basin and, by means of overlay procedures, identifies the water uses in the basin.…”
Section: Water Abstractions Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The water body identification using remote sense data was widely investigated in several geographical contexts. Different satellite platform products were used to compute the NDWI and MNDWI indices (Di Francesco and Giannone, 2019): Landsat images produced an accuracy of extracted water bodies greater than 88 % (Mishra and Prasad, 2015), while for RapidEye imagery the overall accuracy of 95 % was reached (Gideon and Maurice, 2015). Finally, Sentinel-2 multispectral images were tested in Venice coastland (Italy) obtaining an overall accuracy greater than 94 % (Yun et al, 2016) and in the urban area of Beijing and Yantai (China) obtaining an overall accuracy greater than 97 % (Xiucheng et al, 2017).…”
Section: Remote Sensing Techniques For Lake Identificationmentioning
confidence: 99%
“…Conventional policy processes usually draw on setting clear strategies and implying “appropriate” sets of management measures traditionally fed from scientific reports. Good science, however, is likely to be ineffective in producing better management when there are communication failures between scientific knowledge producers and users (Casadei, Pierleoni, & Bellezza, ; Sarewitz & Pielke, ). According to Pahl‐Wostl, Mostert, and Tàbara (), a problem we face when dealing with sustainability does not lay so much in a lack of understanding of how ecological systems function, but rather in a lack of understanding how cultural systems are structured and managed, as well as how they interact with ecological systems.…”
Section: Introductionmentioning
confidence: 99%